Measuring Outcomes of Rehabilitation Among Persons with Upper Extremity Traumatic Injuries - (:unkn) unknown (My University, 2013)
Grip strength is frequently measured to determine outcomes of rehabilitation among people with upper extremity traumatic injuries (UETIs). UETIs also affect rate of force-production during an isometric grip. However, we do not have a reliable and valid measure for detecting these force changes. The purpose of this study was to determine the validity and responsiveness, i.e. ability to detect change, of the Force-Time Curve (F-T Curve) to determine rate of force production. Twenty people with UETIs undergoing rehabilitation were recruited to participate in this study. Using an electronic Jamar dynamometer, each participant performed three maximal isometric grips, each lasting 10 seconds, with their affected hand during an initial session and one month later at a follow-up session. The slopes were calculated using the BioGraph Infiniti software. Our findings found a significant increase in the slopes of force-generation phase (F=5.745, p=0.043) suggesting construct validity, but not for slopes of force-decay phase or peak force. Moderate effect size coefficients were found for slopes of force-generation phase (ES=0.586) and slope of force-decay phase (ES=0.540), indicating moderate responsiveness for these slopes. We recommend the slopes of force-time curve not be used as outcome measures until studies with larger sample and longer duration produce better findings.
Keywords: Force-Time Curve; Grip Strength; Hand Therapy; Strength Training